2021
DOI: 10.3390/life12010044
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 Down-Regulation Reduces VEGF-A Secretion Induced by IGF-1 in ARPE-19 Cells

Abstract: The insulin-like growth factor 1 (IGF-1) stimulates expression and secretion of vascular endothelial growth factor-A (VEGF-A), the main actor in ocular neovascularization, by RPE cells. Activity of IGF-1 is regulated by interaction between its receptor and Caveolin-1 (Cav-1), the main component of caveolae. The aim of this study was to investigate whether modulation of Cav-1 expression affects synthesis and secretion of VEGF-A. ARPE-19 cells were transfected with small interfering RNA for Cav-1 (si-Cav-1) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Specifically, the authors found that down-regulation of CAV-1 reduced constitutive VEGF-A secretion and insulin-like growth factor 1 (IGF-1)-stimulated VEGF-A release. [42] A similar phenomenon was also demonstrated in pancreatic cell lines, in which knockdown of CAV-1 increased insulin secretion under physiological glucose levels. [43] The loss of CAV-1 expression, associated with the disruption of caveolae, was likely linked to the impaired secretion VEGF-A angiogenic factors, suggesting a role of CAV-1 in regulating VEGF-A secretion.…”
Section: Discussionsupporting
confidence: 56%
“…Specifically, the authors found that down-regulation of CAV-1 reduced constitutive VEGF-A secretion and insulin-like growth factor 1 (IGF-1)-stimulated VEGF-A release. [42] A similar phenomenon was also demonstrated in pancreatic cell lines, in which knockdown of CAV-1 increased insulin secretion under physiological glucose levels. [43] The loss of CAV-1 expression, associated with the disruption of caveolae, was likely linked to the impaired secretion VEGF-A angiogenic factors, suggesting a role of CAV-1 in regulating VEGF-A secretion.…”
Section: Discussionsupporting
confidence: 56%
“… 42 , 43 Furthermore, as a major marker of caveolae in endothelial cells, CAV1 are increasing expressed by HIV infection and also interacts with a lot of intracellular signaling molecules such as MAPK and VEGFA. 44 - 46 Therefore, the real functions of these core genes in COVID-19 patients are worthy of investigating and validating in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The release of VEGF-A activates a feedback loop that further enhances NF-kB activation and VEGF-A secretion. Interestingly, we previously demonstrated that Cav-1 depletion reduced basal and IGF-1-induced VEGF-A secretion in retinal pigment epithelial cells [80]. Therefore, it can be hypothesized that the absence of Cav-1 may also reduce VEGF-A secretion in endothelial cells.…”
Section: Cav-1 and Ldl Metabolismmentioning
confidence: 93%